2005
DOI: 10.1111/j.1468-0394.2005.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

A multi-institutional, multinational study of programming concepts using card sort data

Abstract: This paper presents a case study of the use of a repeated single-criterion card sort with an unusually large, diverse participant group. The study, whose goal was to elicit novice programmers' knowledge of programming concepts, involved over

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 8 publications
1
22
0
1
Order By: Relevance
“…This work builds on the study reported in Sanders et al [19] and Petre et al [15](the "bootstrapping study"). In that study, participants were given twenty-six cards, each of which contained the name of a programming concept (listed in Table 1).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…This work builds on the study reported in Sanders et al [19] and Petre et al [15](the "bootstrapping study"). In that study, participants were given twenty-six cards, each of which contained the name of a programming concept (listed in Table 1).…”
Section: Introductionmentioning
confidence: 92%
“…Rugg and McGeorge's [17] tutorial on eliciting knowledge through card sorts specifically includes the categories "other" "not sure" and "not applicable" as ragbag and mentions "don't know", "not sure" and "not applicable" in their recommended instructions to participants. Other than studies specifically referencing Rugg and McGeorge ([14,19,16]), few other studies even mention these categories. None give any analysis of the concepts contained in these categories.…”
Section: Ragbag Categoriesmentioning
confidence: 98%
See 1 more Smart Citation
“…The initial statistical analyses of the study data (reported in [20]) were insufficient to answer the study questions. It was only the subsequent qualitative analysis performed by the South Carolina group, using data collected via the same types of instruments as the original Bootstrap studybut fewer researchers interacting over an extended period of time, both face-to-face and via email-that provided the richer kinds of data needed to answer the original study's questions.…”
Section: Choice Of Analysis Techniquesmentioning
confidence: 99%
“…The range and breadth of the countries and cultures (R1, toprecruiting schools, teaching-oriented institutions, primarily [18][19][20][21][22] year olds, and returning students, etc.) represented in the participating institutions make the results of these works particularly compelling.…”
Section: Population Studiedmentioning
confidence: 99%